2022
DOI: 10.1029/2022gl098547
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Only Reconnection as a Transition From Quiet Current Sheet to Standard Reconnection in Earth's Magnetotail: Particle‐In‐Cell Simulation and Application to MMS Data

Abstract: Standard magnetic reconnection couples with both electron‐ and ion dynamics. Recently, a new type of magnetic reconnection, electron‐only reconnection without the coupling of ion dynamics, has been observed in space. Using a two‐dimensional particle‐in‐cell simulation, we show that in the externally‐driven magnetotail, electron‐only reconnection is a transition from quiet current sheet to standard reconnection. We find that (a) energy conversion j ⋅ E′ is around zero in quiet current sheet but nonzero in elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…It may be useful in the future to consider how the phases of reconnection growth and the energy transport mechanisms discussed here could relate to electron-only vs traditional reconnection. The sequence of events discussed in recent studies [16][17][18] appears similar to the phases of reconnection growth discussed here, especially the increasing strength of the Hall fields, which they identify as a signature of transition from electron-only reconnecting current sheets to traditional reconnection. The increase in the Hall fields during the rapid growth of the reconnection rate in phase 2 is what allows electromagnetic energy to rapidly flow into the exhaust and overcome the bottleneck imposed by the small-scale EDR.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It may be useful in the future to consider how the phases of reconnection growth and the energy transport mechanisms discussed here could relate to electron-only vs traditional reconnection. The sequence of events discussed in recent studies [16][17][18] appears similar to the phases of reconnection growth discussed here, especially the increasing strength of the Hall fields, which they identify as a signature of transition from electron-only reconnecting current sheets to traditional reconnection. The increase in the Hall fields during the rapid growth of the reconnection rate in phase 2 is what allows electromagnetic energy to rapidly flow into the exhaust and overcome the bottleneck imposed by the small-scale EDR.…”
Section: Discussionsupporting
confidence: 74%
“…Some progress has been made relating the structural evolution of the x-line and of phase space to the temporal evolution of the reconnecton rate, including the result that highly structured velocity distribution functions (VDFs) and temperature anisotropies develop in reconnection exhausts close to the occurrence of the maximum reconnection rate 14,15 . Recent studies using MMS data 16,17 and simulations 18 have argued that electron-only reconnection may be understood as a transitional phase between quiet current sheets and traditional electron-ion coupled reconnection in the magnetotail. While these studies did not focus specifically on the growth of the reconnection rate, they identified multiple parameters that appeared to characterize the transition of a time-evolving electron-only current sheet, including increasing current sheet thickness, perpendicular ion temperature, parallel electron temperature, Hall field strength, and the ratio of ion to electron temperature, which grows late in the reconnection process due to the delayed heating of ions compared to electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic of electron‐only reconnection is that there is only electron outflow generated but no ion outflow (e.g., S. Y. Huang et al., 2021; Hubbert et al., 2021; Lu et al., 2022; Yi et al., 2022, and others). We therefore examine the outflow velocity component V z .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Further studies have also reported electron‐only reconnection in the turbulent plasma (Stawarz et al., 2019; Vega et al., 2020), in the bow shock region (Z. Z. Chen et al., 2019; Gingell et al., 2019), within macroscopic magnetic flux ropes (Man et al., 2020), embedded in an ion‐scale current sheet (S. Y. Huang et al., 2021), during the magnetic island coalescence (Yi et al., 2022), and as a transition phase from quiet current sheets to standard reconnection in magnetotail (Hubbert et al., 2021, 2022; Lu et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic reconnection typically forms electron and ion bidirectional outflows. Sometimes, reconnection in turbulent environments at quasi-parallel shocks forms only the electron outflows without any ion outflows, and therefore, such a type of reconnection is referred to as "electron-only" reconnection (Phan et al 2018;Wang et al 2018;Pyakurel et al 2019;Lu et al 2020bLu et al , 2022. Moreover, a tendency that the reconnection electric field increases with the electron outflow speed has been found in a two-dimensional (2D) particle-in-cell (PIC) simulation of the quasi-parallel shock (Bessho et al 2022).…”
Section: Introductionmentioning
confidence: 99%